Single switch rectifier for electric vehicle battery charger application - Mariun, Norman; Nisja, Indra; Aris, Ishak; M. Bashi, Senan (2002)
The static power converter has become very useful in electric vehicle battery charger, because of its ability to convert electrical energy from AC system to DC system. The characteristic of a static power converter as a load is non-linear. Electric vehicle charger is a potential for power quality problems and could have a significant detrimental effect On a utility transmission and distribution line. The major power quality problems may be power factor degradation, current harmonics, and energy efficiency. Recently, a new family of buck-type single switch high power factor rectifier as introduced which has continuous input current and constant output current. By using of multi-resonant scheme, the transistor can operate with zero current switching, and the diodes operate with zero voltage switching. This rectifier is capable of drawing a high quality input current waveform at nearly unity power factor with a single transistor.